Respect Value Found in Turning Red Movie - aditya, Kadek Kenaka; Ni Made Verayanti Utami (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This research focuses on Meilin 's feelings for self - expression and how Meilin respects her ancestors and parents. Meilin is the main character of the novel. It doesn't stop there; Mei is also an active child and excels in school. Mei is always obsessed with making her parents happy until she forgets her own happiness. She couldn't express herself the way she wanted to. However, after going through many events, Mei decided not to hold back anymore. Mei then tried to be more honest with herself, unfortunately it had some effect on her. This is the background of this research by describing the respect that is shown by Meilin towards parents and ancestors qualitatively. The method used in to conduct this study is by observing combined with note-taking techniques. The first step of this research is to watch this film and read the script, after that record every sentence that contains moral values and record how the main character describes these moral values. Moral value of respect was examined using the theory proposed by Linda and Eyre (1993) in their book Teaching Your Children Values. Based on the classification results, the study analyses conversations that contain moral values of respect. shown by the antagonist and protagonist characters in a dialogue